Implementasi Pengolahan Citra Digital Pada Penghitungan Anak Burung Puyuh Menerapkan Metode Blob - Ade Fitri Yana (Journal of Information System Research (JOSH), 2020)
The process of counting quail chicks on farms using manual method is by moving 2 quail chicks on a cardboard that has been provided continuously until the amount specified. Calculations using this method can take a long time and it could be wrong in the calculation so the calculation must be repeated. Digital image is a picture of an object that is analog in the form of video signals on television monitors, mobile phones or is digital that can be directly stored on a storage medium. Digital imagery can also be used as segmentation, counting, detection, tracking and recognition. In this case the digital image will be able to detect the number of quail chicks through several processes before detecting. By using the morphology of dilation and erosion images, it can be done separating overlapping or close together quails. Detection of quail using the BLOB method, in this case a digital image will be able to detect an object that is either moving or not. Blob or blob detection method is detecting a collection of pixel dots that have different colors (lighter or darker).